Peran Sertifikasi Guru terhadap Profesionalisme dan Kesejahteraan Pendidik - Salfa Nur Fadilah; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Government programs for teacher accreditation are designed to enhance the professional standing and well-being of instructors. This investigation seeks to ascertain how teacher accreditation contributes to elevating instructors' skill levels and the caliber of their performance, while also pinpointing difficulties encountered during its execution. The investigation employs a qualitative methodology, incorporating on-site investigations and examinations of existing texts. Information was gathered via discussions, direct observation, record examination, and scholarly article analysis. Methods for analyzing the gathered information encompassed data simplification, information display, and the formulation of conclusions. The findings suggest that the accreditation of teachers positively influences advancements in teaching skills, enthusiasm for work, adherence to rules, and the general welfare of educators. Accredited instructors demonstrate a greater inclination toward actively enhancing their professional proficiencies. Nevertheless, the process of accreditation continues to encounter various impediments, including intricate paperwork, training initiatives that lack practical applicability, and disparities in the distribution of financial incentives for professional development. Consequently, a reassessment and refinement of the accreditation strategy are required to ensure its more successful application and to foster enhancements in the overall quality of national education.